2006
DOI: 10.1016/j.mad.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Methionine flux to transsulfuration is enhanced in the long living Ames dwarf mouse

Abstract: Long-lived Ames dwarf mice lack growth hormone, prolactin, and thyroid stimulating hormone. Additionally the dwarf mice have enzyme activities and levels that combat oxidative stress more efficiently than those of normal mice. We have shown that methionine metabolism in Ames mice is markedly different than in their wild type littermates. In our previous work we hypothesized that the flux of methionine to the transsulfuration pathway is enhanced in the dwarf mice. The current study was designed to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 29 publications
7
59
0
1
Order By: Relevance
“…The strongest evidence comes from studies in rats and mice in which amino acids are fed in lieu of protein, where restriction of dietary methionine alone can extend maximum lifespan by 10-45% (Orentreich et al 1993;Richie et al 1994;Zimmerman et al 2003;Miller et al 2005). Methionine metabolism is abnormal in long-lived mutant mice that are deficient in growth hormone, prolactin and thyroid stimulating hormone (Uthus and Brown-Borg 2003;Brown-Borg et al 2005;Uthus and Brown-Borg 2006). Furthermore, methionine restriction specifically inhibits the induction of IGF-I expression by growth hormone in pig hepatocytes (Stubbs et al 2002), indicating a potential regulatory interaction of methionine metabolism on the growth hormone-IGF-I signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest evidence comes from studies in rats and mice in which amino acids are fed in lieu of protein, where restriction of dietary methionine alone can extend maximum lifespan by 10-45% (Orentreich et al 1993;Richie et al 1994;Zimmerman et al 2003;Miller et al 2005). Methionine metabolism is abnormal in long-lived mutant mice that are deficient in growth hormone, prolactin and thyroid stimulating hormone (Uthus and Brown-Borg 2003;Brown-Borg et al 2005;Uthus and Brown-Borg 2006). Furthermore, methionine restriction specifically inhibits the induction of IGF-I expression by growth hormone in pig hepatocytes (Stubbs et al 2002), indicating a potential regulatory interaction of methionine metabolism on the growth hormone-IGF-I signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…72 Also in agreement with a methionine role in aging, it has been reported that long-lived Ames dwarf mice have an altered methionine metabolism showing a marked increase in the transulfuration pathway compared to their wild-type siblings. 73 All the above results point to methionine as the single dietary factor responsible for part of the longevity extension effect of DR.…”
Section: Effect On Longevitymentioning
confidence: 89%
“…However, to date, most of the data available on BHMT regulation come from early studies on the effects exerted in the whole methionine cycle by several hormonal treatments. Increases in BHMT activity and mRNA levels were observed by the action of hydrocortisone, cortisol and triamcinolone, whereas growth hormone only induced BHMT mRNA [18,34,65,[70][71][72][73][74][75][76].…”
Section: Bhmt Regulationmentioning
confidence: 96%